STEREOTIP TENTANG DIFABEL: SEBUAH PERSPEKTIF KOMUNIKASI LINTAS BUDAYA - Wicaksono, Drajat; Suryandari, Nikmah; Camelia, Allyvia (Master of Communication Science Program, Universitas Diponegoro, 2021)
This paper will describe the study of stereotypes in persons with disabilities, from the perspective of intercultural communication. During this time people with disabilities often get a bad stigma and are still underestimated as a party that needs to be pitied. For families, sometimes people with disabilities are considered a disgrace that needs to be covered up. The assumption that people with disabilities are different and even abnormal is shown as a form of negative perception that is nothing but part of the stereotype. Stereotype is not only from the labeling process of the community, but also the labeling process carried out by the diffable to himself who is aware of the disabilities that he has. Communication difficulties will arise from stereotyping, which generalizes people based on little information and shapes people's assumptions based on their membership in a group. In other words, stereotyping is the process of placing people into established categories, or judgments about people or objects based on appropriate categories, rather than on their individual characteristics. In the study of intercultural communication, stereotyping is the categorization of a group in general by ignoring individual differences. These groups include: racial groups, ethnic groups, the elderly, various professional occupations, or people with certain physical appearance. Stereotype does not view individuals in the group as unique people or individuals